Pengaruh Model Teams Games Tournament (TGT) Berbantuan Permainan Ular Tangga Terhadap Keterampilan Kolaboratif dan Hasil Belajar Peserta Didik Kelas VII SMP - Fitriani, Sukma; Yanto, Febri; Azzahra, Firda; Wati, Fatma (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop collaborative skills and learning outcomes of junior high school students in grade VII tested using the Team Games Tournament (TGT) learning paradigm assisted by snakes and ladders media. This research is a quantitative research, using a quasi-experimental method with a nonequivalent control group design. All seventh-grade students enrolled in the 2024–2025 academic year at UNP Laboratory Development Junior High School became the study population. Sampling used a purposive sampling approach. Classes VII A and C each served as the control and experimental groups in this study. The instruments in the study were a collaborative skills questionnaire and a learning outcome test. Data were analysed descriptively quantitatively. From the results of the hypothesis test for the collaborative skills posttest in the self-assessment assessment, the t-count (2.21) was obtained > t-table (2.00). Meanwhile, in the peer assessment assessment, the t-count (2.19) was obtained > t-table (2.00). In addition, according to the results of the hypothesis test for the learning outcome posttest, it showed that t-count (2.13) > t-table (2.00), showing that the two groups, experimental and control, differed significantly from each other. The conclusion is that student learning outcomes and collaborative skills in science are positively influenced by the TGT model when the snakes and ladders game is used as an aid